Patient capital : the role of family firms in sustainable business - Sharma, Sanjay, 1955-; Sharma, Pramodita (Cambridge : Cambridge University Press, 2019)
Sustainable businesses create economic and social value while simultaneously protecting the natural environment for future generations. This examination of environmental sustainability through the lens of the family business identifies factors that help family and non-family organizations address the dilemma of balancing short-term productivity, efficiency and profitability objectives, with innovating for long-term sustainable value creation. Exploring the case of the wine industry - an industry characterized by a variety of governance systems - Sanjay and Pramodita Sharma develop fresh insights into influences and drivers for proactive environmental strategies to address major global sustainability challenges. By doing so, the authors are able to demonstrate that family firms with a focus on trans-generational continuity of business, long temporal orientation, shared vision, faster decision-making processes, and the goal of preserving socio-emotional wealth are more likely to make patient long-term investments for innovations in products, services, processes and business models to address environmental sustainability challenges.
Title from publisher's bibliographic system (viewed on 05 Jul 2019).
Keywords: Family-owned business enterprises -- Environmental aspects; Sustainable development; Management -- Environmental aspects